Diagnostic characteristics of Xpert MTB/RIF assay for the diagnosis of tuberculous meningitis and rifampicin resistance in Southern Brazil - Sergio Monteiro de Almeida; Gislene Maria Botão Kussen; Laura Cogo; José Henrique Carvalho; Keite Nogueira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: The timely diagnosis of tuberculous meningitis (TBM) is challenging. Molecular diagnostic tools are necessary for TBM, particularly in low- and middle-income countries. Objectives: We aimed to calculate the diagnostics characteristics of Xpert MTB/RIF for the detection of Mycobacterium tuberculosis in the cerebrospinal fluid (CSF) and the frequency of rifampicin (RIF)-resistance in the CSF samples. Methods: A total of 313 consecutive CSF samples were studied and categorized into TBM definite, probable, possible, or not TBM cases based on the clinical, laboratory, and imaging data. Results: For the definite TBM cases (n=7), the sensitivity, specificity, efficiency, and positive likelihood ratio were 100, 97, 97, and 38%, respectively. However, for the TBM definite associated with the probable cases (n=24), the sensitivity decreased to 46%. All CSF samples that were Xpert MTB/RIF-positive were RIF susceptible. Conclusion: Xpert MTB/RIF showed high discriminating value among the microbiology-proven TBM cases, although the values for the probable and possible TBM cases were reduced. Xpert MTB/RIF contributes significantly to the diagnosis of TBM, mainly when coupled with the conventional microbiological tests and clinical algorithms.